Electronic Health Literacy and Self-Efficacy Among Primary and Middle School Students in China: A Moderated Mediated Analysis - Lin Tian; Tao Xie; Jinnan Liu; Ying Mao (Children)
Background: The Internet has become a crucial tool for learning, socializing, and entertainment for contemporary minors, and plays an increasingly prominent role in their growth. However, it has been observed that students are often unable to make good judgments about online health information and barely use the Internet to help tackle their health problems. The purpose of this study was to determine the relationship between electronic health literacy (EHL) and general self-efficacy among Chinese primary and middle school students. Methods: A total of 1200 questionnaires were sent out, and 1085 effective questionnaires were received with effective recovery of 90.42%. First, we conducted a confirmatory factor analysis. Second, structural equation modeling (SEM) was used to explore the mechanisms underlying the relationship between EHL and general self-efficacy. Results: The results revealed a significant positive correlation between EHL and self-efficacy. The results of the CFA showed a good fit for the data. The results of SEM showed that the relationship between self-efficacy and health information applications was partially mediated by health information acquisition (β = 0.47, [Bias-Corrected 95%CI: 0.39, 0.59], [Percentile 95%CI: 0.37, 0.58]). Household factors moderated this mediating relationship (β = 0.4, [Bias-Corrected 95%CI: 0.19, 0.61], [Percentile 95%CI: 0.19, 0.61]). Conclusions: Information acquisition was found to play a mediating role between self-efficacy and information application. Household factors moderated the indirect relationship between self-efficacy and information applications through information acquisition.